Evaluating Successful Pregnancy Outcome in Women Undergoing Trial of Labour after Caesarean Section (TOLAC) - Shazia Iffet; Ayesha Arif; Sadaf Moin; Surayya Jabeen; Samina Rehan (Journal of Bahria University Medical and Dental College)
Objective: To determine the successful pregnancy outcome in women who opted for trial of labour after one lower segment transverse caesarean section (TOLAC).